Two functions f and g are defined by f:x→3x+2 and g:x→x^2-2.Obtain expressions for fg and gf.Find the value(s) of x for which

f=g?

fg=gf?

1 answer

f(g) = 3g+2 = 3(x^2-2)+2 = 3x^2-4
g(f) = f^2-2 = (3x+2)^2-2 = 9x^2+12x+2

f=g when 3x+2=x^2-2, or 4 or -1
fg=gf when 3x^2-4 = 9x^2+12x-2, or -1±√(2/3)
Similar Questions
    1. answers icon 1 answer
  1. Two functions g and h are defined as :g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x)
    1. answers icon 0 answers
  2. Two functions g and h are defined as :g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x) b) g inverse 1(x)
    1. answers icon 0 answers
  3. Two functions g and h are defined as :g:x--> 2x+3/x-4 h:x --> 1/x Write expressions for : a) hg(x) b) g inverse 1(x)
    1. answers icon 1 answer
more similar questions